Implementasi Algoritme Acorn untuk Pengamanan Data pada WSN - Nadya Puspitasari; Ari Kusyanti; Fariz Andri Bakhtiar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
The Wireless Sensor Network (WSN) has brought Internet of Things (IoT) into a new era because the sensor network that developed by WSN will be using various communication protocols. WSN also performs several communication models, one of WSN's communication models is a master-slave communication model which is a node-to-node communication model. LoRa is one of the technological development at WSN, which scope wide area and has low power consumption. The use of LoRa is very common nowadays, but LoRa's communication remains unsafe. Without security in LoRa, an intruder can obtain data by sniffing. Data protection is an important issue in the implementation of IoT so the data transferred by LoRa must be secured. An encryption algorithm such as Acorn algorithm can be used to secure data. Besides being able to transform data into new forms, the Acorn algorithm can also generate tags to check the authenticity of the data. The data communication on LoRa using the master-slave communication model can be secured by implementing the algorithm. This is proven by the results of research carried out through sniffing attacks and also active attacks called Known Plaintext Attacks (KPA). Sniffing attacks carried out after the implementation of the Acorn algorithm is only capable of producing encrypted data. As a result of attacks with known-plaintext attacks, attacks do not succeed in getting keys from related ciphertext and plaintext. It can be concluded from the test results by sniffing attacks and known-plaintext attacks that the implementation of the Acorn algorithm has succeeded in securing the data sent by LoRa.